Spinach, Malabar—Basella rubra L. - James M. Stephens (EDIS)
This document describes Malabar spinach (Basella rubra L.), a tropical vine with spinach-like leaves used in cooking. Originating from India, it thrives in warm, moist climates and can be grown from seeds or cuttings. Though not a true spinach, it is valued for its edible, fleshy leaves and ornamental appeal. The plant grows well in various soils and benefits from trellising and light shade. Commonly used in Bengali cuisine, it is less slick in texture than traditional spinach when cooked. Original publication date May 1994.